Whole body vibration improves body mass, flexibility and strength in previously sedentary adults - Kholvadia, A; Baard, ML (South African Journal of Sports Medicine, 2012)
Objectives. This study aimed to determine the effectiveness of whole body vibration (WBV) training for promoting healthrelated physical fitness in sedentary adults. Design. A non-randomised sampling technique was used with an equivalent match-pair comparison group, pre- and posttest design. Volunteers were gathered through a combination of accidental and snowball sampling and divided into either the experimental (n=32) or control group (n=30). Dependent variables included body mass, hamstring flexibility as measured by the sit-and-reach test, upper-body strength as measured by a grip strength dynamometer, abdominal and upper-body muscular endurance as measured by 1-minute timed sit-up and push-up tests, respectively. The standardised YMCA fitness battery was used as the evaluation protocol. The WBV experimental group participated in a progressive 3 times/week training programme for a maximum duration of 30 minutes/session for 12 consecutive weeks. The control group remained sedentary. Results. Significant improvements in all five of the selected dependent parameters were measured. Conclusion. WBV training 3 times weekly for 30 minutes/session provides an effective method of exercise intervention for health promotion in sedentary adults over a 12-week period.